Effect of tetramethylpyrazine on P-selectin and hepatic/renal ischemia and reperfusion injury in rats - Chen, Jin-Lian (World J Gastroenterol, 2003)
AIM: To investigate the effect of tetramethylpyrazine on hepatic/renal ischemia and reperfusion injury in rats. METHODS: Hepatic/renal function, histopathological changes, and hepatic/renal P-selectin expression were studied with biochemical measurement and immunohistochemistry in hepatic/renal ischemia and reperfusion injury in rat models. RESULTS: Hepatic/renal insufficiency and histopathological damage were much less in the tetramethylpyrazine-treated group than those in the saline-treated groups. Hepatic/renal P-selectin expression was down regulated in the tetramethylpyrazine-treated group. CONCLUSION: P-selectin might mediate neutrophil infiltration and contribute to hepatic/renal ischemia and reperfusion injury. Tetramethylpyrazine might prevent hepatic/renal damage induced by ischemia and reperfusion injury through inhibition of P-selectin.